2015
DOI: 10.1039/c4sc01953a
|View full text |Cite
|
Sign up to set email alerts
|

Photoaffinity labeling of transcription factors by DNA-templated crosslinking

Abstract: A dual-probe system can specifically capture DNA-binding proteins with an unmodified binding site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 92 publications
(114 reference statements)
0
31
0
Order By: Relevance
“…It is also worth noting that the approach used by Yao et al. was able to capture indirectly binding targets in the protein complex; a highly useful capability that has yet to be explored with the DPAL method (e.g., varying the site of CP hybridization on the BP DNA). Currently, we are studying other potential targets reported in Figure c to investigate their binding modes with MLN8237 (direct or indirect) and functional connections with the biological activities of MLN8237.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also worth noting that the approach used by Yao et al. was able to capture indirectly binding targets in the protein complex; a highly useful capability that has yet to be explored with the DPAL method (e.g., varying the site of CP hybridization on the BP DNA). Currently, we are studying other potential targets reported in Figure c to investigate their binding modes with MLN8237 (direct or indirect) and functional connections with the biological activities of MLN8237.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the groups of Hosoya, Suzuki, and Young designed several types of highly compact “all‐in‐one” affinity probes for target ID; Yao and co‐workers developed a “minimalist” linker strategy to minimize the impact of add‐on structures on target binding; and the group of Cravatt designed a series of fully functionalized small‐molecule probes that incorporated the cross‐linker as part of the binding structure . Previously, we reported a DNA‐based affinity labeling method named DPAL . Instead of using a single trifunctional probe, DPAL has a dual‐probe system: a BP, in which the small molecule is conjugated with a short DNA strand, and a CP, in which the affinity tag and the cross‐linker are conjugated with a complementary DNA strand (Figure b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we confirmed that this salt effect also works with non-DNA-based probes and probes with benzophenone and phenylazide, two other commonly used photo-crosslinkers. We have been applying this salt effect when characterizing small molecule-protein and DNAprotein interactions (Li et al 2013a(Li et al , 2014bLiu et al 2015).…”
Section: The Salt Effectmentioning
confidence: 98%
“…Furthermore, we have developed the second generation of DPAL by utilizing the multivalency effect; ) a trivalent arylazide crosslinker has significantly improved the labeling yield of DPAL (Li et al 2014b). In addition, recently we extended the application of DPAL to study DNAbinding proteins, such as transcription factors and proteins recognizing epigenetic marks (Liu et al 2015).…”
Section: Dna-programmed Affinity Labeling (Dpal)mentioning
confidence: 99%